The state effects of enviromental policy in indigenous territories - Biffi Isla, Valeria (2021)
Based on the implementation of a forest conservation program in indigenous communities analyze how the indigenous population understands the state as an environmental ruling institution and how they perform as users of public policy. The results of this ethnographic study suggest that the implementation of this scheme of economic incentives for conservation generates a weak connection of the state as an environmental institution but reinforces the role of the state as a provider of development opportunities. With this scheme, the indigenous population has constructed alternative interpretations of forest conservation as an asset to attract future development opportunities and of economic incentives as rewards and tips. The main state effect of the program is the bureaucratisation of communities to adapt then to the state ideal of installing an audit culture.